FACTORS AFFECTING COMPETITIVE SAPROPHYTIC ACTIVITY OF FUSARIUM UDUM, THE CAUSAL ORGANISM OF WILT OF PIGEONPEA - PRASANTA K. SEN GUPTA, D. MUKHOPADHYAY and (Indian Phytopathology, 2002)
Competitive saprophytic activity (CSA) of Fusarium udum, as evidenced by colonization of pigeon pea stem pieces in inoculated soil, increased with increased inoculum density in soil upto 7 per cent. Substrate enrichment with low concentration (0.5 per cent) of urea and dextrose reduced the CSA but enrichment with higher concentration of these chemicals (1-2 per cent) increased the CSA. Temperature of 20 and 35Â°C were found to be optimum for’ CSA of F. udum. High soil moisture was found to be .detrimental to CSA. Amendment of soil with dextrose increased, but that with mustard cake reduced CSA.